2018
DOI: 10.1098/rsos.180392
|View full text |Cite
|
Sign up to set email alerts
|

High-performance single-walled carbon nanotube transparent conducting film fabricated by using low feeding rate of ethanol solution

Abstract: We report floating catalyst chemical vapour deposition synthesis of single-walled carbon nanotubes (SWCNTs) for high-performance transparent conducting films (TCFs) using low feeding rate of precursor solution. Herein, ethanol acts as carbon source, ferrocene and thiophene as catalyst precursor and growth promoter, respectively. By adopting a low feeding rate of 4 µl min−1, the fabricated TCFs present one of the lowest sheet resistances of ca 78 Ω sq.−1. at 90% transmittance. Optical characterizations demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…2(c) and Fig. S2 in the ESM), which also occurs in our ethanol system [10,17]. Ma et al [27] suggested that an excess of hydrogen induced fast decomposition of the hydrocarbons (ortho-xylene and acetylene were chosen as a hybrid carbon source), resulting in the accumulation of carbon byproducts on the catalyst surface and slowing down the nanotube growth process.…”
Section: Effects Of H 2 and N 2 On Swcnt Yield And Diametersupporting
confidence: 62%
See 4 more Smart Citations
“…2(c) and Fig. S2 in the ESM), which also occurs in our ethanol system [10,17]. Ma et al [27] suggested that an excess of hydrogen induced fast decomposition of the hydrocarbons (ortho-xylene and acetylene were chosen as a hybrid carbon source), resulting in the accumulation of carbon byproducts on the catalyst surface and slowing down the nanotube growth process.…”
Section: Effects Of H 2 and N 2 On Swcnt Yield And Diametersupporting
confidence: 62%
“…The description of the four point probe system for sheet resistance measurement can be found elsewhere [10]. Each sheet resistance data point is the average of three measurement values from different parts of the SWCNT film.…”
Section: Swcnt Filmsmentioning
confidence: 99%
See 3 more Smart Citations